AL-QUR'AN SEBAGAI TEKS YANG HIDUP: Dinamika Hafalan dan Transmisi Lisan di Era Modern - Abdul Mufid; Wan Khairul Aiman Wan Mokhtar (AL ITQAN: Jurnal Studi Al-Qur'an, 2023)
The Qur'an, as a living text, has continually adapted to the socio-cultural dynamics of diverse eras, including the challenges and opportunities presented by modernity. This study explores the dynamics of Qur'anic memorization and oral transmission in the modern era, focusing on how these practices navigate the tension between tradition and technological advancements. The research is guided by the central question how have modern tools and societal changes influenced the practice and perception of Qur'anic memorization and oral transmission. Qualitative methods with an ethnographic approach were used in this study. The findings reveal that while technological tools, such as digital Qur'an applications and online platforms, have facilitated access and learning, they also pose challenges to traditional methods, such as face-to-face teacher-student interactions.